Hesperetin Exhibits Anti-Inflammatory Effects on Chondrocytes via the AMPK Pathway to Attenuate Anterior Cruciate Ligament Transection-Induced Osteoarthritis - Wu, Jiaqin; Qian, Yuna; Chen, Cheng; Feng, Fan; Pan, Lianhong; Yang, Li; Wang, Chunli (Frontiers in Pharmacology, 2021)
This study aimed to determine whether Hesperetin (HPT) has chondroprotective effects against TNF-α-induced inflammatory response of chondrocytes and related mechanisms and clarify the impact of HPT on osteoarthritis (OA) induced by anterior cruciate ligament transection (ACLT). Under tumor necrosis factor-α (TNF-α) stimulation, rat chondrocytes were treated with or without HPT. The CCK-8 assay was used to detect viability and cytotoxicity. RT-qPCR and Western blot were used to examine the expression of aggrecan, collagen type II, and inflammatory and proliferative genes/proteins in chondrocytes. Flow cytometry was used to check the cell cycle to determine whether HPT protects chondrocytes against the inhibitory effect of TNF-α on chondrocyte proliferation. In addition, RNA sequencing was used to discover possible molecular targets and pathways and then validate these pathways with specific protein phosphorylation levels. Finally, immunofluorescence staining was used to examine the phosphorylation of the AMP-activated protein kinase (AMPK) pathway. The results showed that HPT restored the up-regulation of interleukin 1β (IL-1β), PTGS2, and MMP-13 induced by TNF-α. In addition, HPT reversed the degradation of the extracellular matrix of chondrocytes induced by TNF-α. HPT also reversed the inhibitory effect of TNF-α on chondrocyte proliferation. RNA sequencing revealed 549 differentially expressed genes (DEGs), of which 105 were up-regulated and 444 were down-regulated, suggesting the potential importance of the AMPK pathway. Progressive analysis showed that HPT mediated the repair of TNF-α-induced chondrocyte damage through the AMPK signaling pathway. Thus, local treatment of HPT can improve OA induced by ACLT. These findings indicated that HPT has significant protective and anti-inflammatory effects on chondrocytes through the AMPK signaling pathway, effectively preventing cartilage degradation. Given the various beneficial effects of HPT, it can be used as a potential natural drug to treat OA.